(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
This article examines the peculiarities of the professional competences of the teacher as a subject of upbringal interaction with the student in the context of the problems of psycho-pedagogical design. The article presents the results of the experimental study of pupils expectations regarding the professional competencies of the educators, the indicators of the level of parenting of pupils as subjects of the upbringal situation and the peculiarities of their relationship with the teacher are presented.